Early anthropoid femora reveal divergent adaptive trajectories in catarrhine hind-limb evolution - Sergio Almécija (Nature Portfolio, 2019)
The proximal femur is key for understanding locomotion in primates. Here, the authors analyze the evolution of the proximal femur in catarrhines, including a new Aegyptopithecus fossil, and suggest that Old World monkeys and hominoids diverged from an ancestral state similar to Aegyptopithecus.